2014
DOI: 10.1111/1744-9987.12164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2‐Week Versus 4‐Week Dosing Intervals of Epoetin Beta Pegol on Erythropoiesis and Iron Metabolism in Hemodialysis Patients

Abstract: Epoetin beta pegol (a continuous erythropoietin receptor activator; CERA) is usually administered once in 4 weeks or once monthly. However, the optimal dosing interval remains unknown. We, therefore, compared the effect of CERA administration between dosing intervals of 2 weeks (TWICE group) and 4 weeks (ONCE group) on erythropoiesis and iron metabolism in 20 hemodialysis patients. CERA was administered intravenously at weeks 0 and 2 for the TWICE group, and at week 0 for the ONCE group. Levels of hemoglobin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
3
18
1
Order By: Relevance
“…Morikami et al have recently reported finding that biweekly administration of CERA showed a significant decrease in serum ferritin levels in association with temporal changes in TSAT in Japanese HD patients [18]. The results of the present study showed that switching from DA to CERA did not alter the subjects' serum ferritin levels with a slight fluctuation in TSAT levels during the follow-up period.…”
Section: Discussionsupporting
confidence: 54%
“…Morikami et al have recently reported finding that biweekly administration of CERA showed a significant decrease in serum ferritin levels in association with temporal changes in TSAT in Japanese HD patients [18]. The results of the present study showed that switching from DA to CERA did not alter the subjects' serum ferritin levels with a slight fluctuation in TSAT levels during the follow-up period.…”
Section: Discussionsupporting
confidence: 54%
“…Although conversion to CERA with intervals of once every 2 weeks (Q2W) or 4 weeks (Q4W) from other ESAs is achieved safely in hemodialysis patients and oncemonthly administration is recommended in Japan, the optimal interval of CERA administration is not known. Recently, it is reported that more continuous erythropoiesis was achieved with a Q2W administration of CERA than Q4W [7], and Q2W administration of CERA is more effective than Q4W to achieve target hemoglobin (Hb) levels [8]. Although we also reported more effective erythropoiesis of CERA by Q2W than Q4W, the fluctuation of Hb levels during Q4W is greater than that during Q2W [9], which makes it difficult to compare the true effect of the interval of CERA administration on Hb levels.…”
Section: Introductionmentioning
confidence: 73%
“…Although the precise mechanisms are not clear, in hemodialysis patients, ESA administration exerts a biphasic pattern of serum hepcidin-25 levels; early upregulation followed by late downregulation [14], and low serum hepcidin levels Variables are represented as mean ± standard deviation HD hemodialysis, BUN blood urea nitrogen, Cr creatinine, TP total protein, Alb albumin, Hb hemoglobin, CRP C-reactive protein, Fe iron facilitate iron utilization, which results in a decrease of serum ferritin levels. The degree of iron utilization and recruitment to the hematopoietic system seems to differ according to the type of ESAs [14][15][16] and interval of dosing [7,8]. Transient reduction of serum hepcidin and ferritin levels induced by CERA administration reach a maximum around 1 week after dosing and return to pre-administration levels by 4 weeks, with this being the rationale of the once-monthly administration of CERA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of iron utilization could play some role more increasing of Hb level in patients with long-acting ESA than those of short-acting ESA. Actually, it is reported that difference of type of ESA [18] or difference of administration interval of ESA [19] make a changing of iron status favorably for treatment of anemia in ESKD patients. However, any remarkable differences did not BMI body mass index, BP blood pressure, CTR cardiothoracic ratio, eGFR estimated glomerular filtration rate, HDL-C high density lipoprotein, i-PTH intact parathyroid hormone, CRP c-reactive protein, TIBC total iron-binding capacity, ESA erythropoiesis-stimulating agents, ARB angiotensin receptor blocker, ACE-I angiotensin-converting enzyme inhibitor exist between two patients group with long-acting ESA and short-acting ESA in the marker of iron status such as iron, ferritin, TSAT, and usage of iron agents.…”
Section: Assessment Of the Effects Of Long-acting Esa On Hb Levelmentioning
confidence: 99%